Absolute Theta Power in the Frontal Cortex During a Visuomotor Task: The Effect of Bromazepam on Attention. (October 2015) - Gongora, Mariana; Peressuti, Caroline; Velasques, Bruna; Bittencourt, Juliana; Teixeira, Silmar; Arias-Carrión, Oscar; Cagy, Mauricio; Ribeiro, Pedro
Bromazepam is a benzodiazepine, which has been widely employed in the treatment of anxiety. We investigated the electrophysiological changes in absolute theta power within the frontal cortex when individuals performed a visuomotor task under bromazepam. The sample of 17 healthy individuals was randomized into 2 experimental conditions, under which bromazepam 6 mg and placebo were administered on different days. All subjects were right -handed, with no mental or physical illness and were not using any psychoactive or psychotropic substance during the entire period of the study. We found an increase in reaction time under bromazepam compared with placebo . With regard to the electrophysiological variable, we found a lower theta power value in the prefrontal cortex prior to task execution, compared with after. We therefore suggested that this could be an increase of neural activity in this region, because of the subjects' readiness to perform the task, that is, because of their higher alertness. The right lateral frontal region showed lower theta power under bromazepam for pre- and post-finger movement. This could have occurred because of more effort to execute the task. In the left frontal region: premovement did not demonstrate any difference between conditions, possibly because the proposed task was simple to execute. In conclusion, theta power plays an important role in the analysis of visuomotor performance, assuming that bromazepam causes impairment on sustained attention and sensory perception.